2020
DOI: 10.1080/15384101.2020.1804232
|View full text |Cite
|
Sign up to set email alerts
|

TRIM71 binds to IMP1 and is capable of positive and negative regulation of target RNAs

Abstract: TRIM71 is an important RNA-binding protein in development and disease, yet its direct targets have not been investigated globally. Here we describe a number of disease and developmentallyrelevant TRIM71 RNA targets such as the MBNL family, LIN28B, MDM2, and TCF7L2. We describe a new role for TRIM71 as capable of positive or negative RNA regulation depending on the RNA target. We found that TRIM71 co-precipitated with IMP1 which could explain its multiple mechanisms of RNA regulation, as IMP1 is typically thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…A very recent study has shown that TRIM71 is able to bind and stabilize specific mRNAs in the HCC cell line HepG2 47 . Beyond the fact that we found some of these mRNAs to be let-7 targets, our work also confirms that TRIM71 is capable of positively regulating mRNA expression post-transcriptionally in ESCs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A very recent study has shown that TRIM71 is able to bind and stabilize specific mRNAs in the HCC cell line HepG2 47 . Beyond the fact that we found some of these mRNAs to be let-7 targets, our work also confirms that TRIM71 is capable of positively regulating mRNA expression post-transcriptionally in ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM71 is upregulated in patients with hepatocellular carcinoma (HCC) and its expression is correlated with advanced tumor stages and poor prognosis 24,44 . Several studies have shown that TRIM71 promotes proliferation in several HCC cell lines, including HepG2, Hep3B and Huh7 24,44,47 . In one of these studies, an increase of let-7 activity was observed in TRIM71 knockdown cells 44 .…”
Section: Trim71 Binds and Stabilizes Let-7 Mrna Targets In Hcc Cellsmentioning
confidence: 99%
See 3 more Smart Citations